First national analysis of severe obesity hospitalizations in Italy: insights from discharge card database - Valerio Manno; Valentina Minardi; Maria Masocco; Francesco Cobellis; Giada Minelli; Donato Greco (Frontiers Media S.A., 2024)
BackgroundObesity is associated with numerous severe diseases necessitating intensive healthcare for diagnosis and treatment. Most patients with obesity, especially in its severe form, require at least one hospitalization. However, few studies in Italy have assessed the burden of obesity on the National Health System. This study aims to routinely estimate the 'disease burden' by analyzing hospital admissions related to severe obesity.SubjectsWe analyzed the medical records of the Italian national hospital discharge database, including all patients older than 18 years discharged with the diagnosis of 'severe obesity'.' We included patients who underwent bariatric surgery, even without an explicit obesity code, such as laparoscopic restrictive gastric procedures, other stomach operations, and high gastric bypass. Special focus was given to those who underwent abdominal reshaping surgery. The cross-sectional survey PASSI in Italy served as an additional data source to estimate. The phenomenon was described using appropriate indicators, including rates and ratios between rates. Linear regression was employed to analyze trends in standardized rates over time.ResultsBetween 2014 and 2021, a total of 243,325 patients were discharged with a severe obesity code in Italy. Among these patients, 36.8% underwent at least one bariatric surgery procedure. We investigated the types of bariatric surgery procedures performed. The most frequent procedure was "other operations on the stomach," where sleeve gastrectomy is included which also appears to be steadily increasing during the study period together with the gastric bypass, while the gastric bondage is decreasing over time.ConclusionThese findings underscore the significant burden of severe obesity on Italy's healthcare system, a burden that is progressively increasing. The growing utilization of bariatric surgery suggests an escalating trend toward adopting drastic solutions to combat this health issue.